Carbonic anhydrase from Apis mellifera: purification and inhibition by pesticides - Ercan Soydan; Ahmet Güler; Selim Bıyık; Murat Şentürk; Claudiu T. Supuran; Deniz Ekinci (Taylor & Francis Group, 2017)
Carbonic anhydrase (CA) enzymes have been shown to play an important role in ion transport and in pH regulation in several organisms. Despite this information and the wealth of knowledge regarding the significance of CA enzymes, few studies have been reported about bee CA enzymes and the hazardous effects of chemicals. Using Apis mellifera as a model, this study aimed to determine the risk of pesticides on Apis mellifera Carbonic anhydrase enzyme (Am CA). CA was initially purified from Apis mellifera spermatheca for the first time in the literature. The enzyme was purified with an overall purification of ∼35-fold with a molecular weight of ∼32 kDa. The enzyme was then exposed to pesticides, including tebuconazole, propoxur, carbaryl, carbofuran, simazine and atrazine. The six pesticides dose-dependently inhibited in vitro AmCA activity at low micromolar concentrations. IC50 values for the pesticides were 0.0030, 0.0321, 0.0031, 0.0087, 0.0273 and 0.0165 μM, respectively. The AmCA inhibition mechanism of these compounds is unknown at this moment.